Profeten Jeremias og genopbyggelsen af national identitet - Holt, Else K. (Dansk Teologisk Tidsskrift, 2010)
The Book of Jeremiah can be read as a contribution to the struggle for the rebuilding of the exilic and post-exilic nation of Israel. Based on social-anthropological theories about the conditions of the life of refugees, presented by the American biblical scholar Daniel Smith-Christopher, the polyphonic Book of Jeremiah is presented as a text with a “V-structure”: The first half of the book represents a dystopian disclosure of Israel’s culpability while the second offers a utopian message of hope for the nation. Such a message needs authority, and this authority is reinforced by the strong identification of the prophet with (the word of) God. This article presents the literary persona of the prophet as partly dissimilated from the people and assimilated to God and partly in conflict with God as a role model for the people in its suffering.